TAICHI EFFICACY FOR INCREASING BETA ENDORPHIN IN THE AGING PROCESS: LITERATURE REVIEW - Arnylia Djunaidy; Wilianto W; I Putu Gede Adiatmika (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2023)
The aging process can be delayed by exercises such as taichi and meditation. They are useful for reducing oxidative stress, inflammation and cellular aging. The older people will be more fit and happy. One of the parameter is ?-endorphin. This literature review will investigate the effect of taichi determined by beta- endorphin in the aging process. Google Scholar, Researchgate, and Mendeley were used as the search engine. The keywords were taichi, endorphin, & anti-aging. The effect of taichi on geriatric beta-endorphin were analyzed from 7 articles. Body homeostasis, organ systems, and other changes will reduce the functional capacity from the cellular to individual level in the aging process. To delay the physiological process of aging, taichi can improve the cognitive, endocrine, musculoskeletal, cardiovascular, and immunological organ system. The endorphin change will show the effect of taichi for a better quality of aging process.